A Study on the Eigenmodes Constructed in the Double Ridge Waveguide - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
In this study, the eigenmodes of a double ridge waveguide has been investigated by finite element method. The eigenmodes are schematically represented by the electric field, 3D electric potential and equipotential contour. The electric field together with the electric potential compensate each other in understanding the eigenmodes. The eigenmodes are divided into two classes: transverse electric modes and transverse magnetic modes. They are determined by the intensity of electric field and the peak position of electric potential. The several prominent eigenmodes from the lower order are placed in the spectra. They are more complicated by boundary conditions than single-ridged waveguides. By symmetrically arranging the two ridges up and down, the eigenmodes show various shapes in the double ridge waveguide. Since the waveguide forms a bilaterally symmetrical structure with respect to the center line, the eigenmodes exhibit such a symmetrical shape.